NKG2A Down-Regulation by Dasatinib Enhances Natural Killer Cytotoxicity and Accelerates Effective Treatment Responses in Patients With Chronic Myeloid Leukemia - Chang, Ming-Chin; Cheng, Hung-I; Hsu, Kate; Hsu, Yen-Ning; Kao, Chen-Wei; Chang, Yi-Fang; Lim, Ken-Hong; Chen, Caleb Gonshen (Frontiers in Immunology, 2019)
Chronic myeloid leukemia (CML) is a hematological malignancy characterized by the presence of t(9;22) chromosomal translocation that results in BCR-ABL fusion gene. ABL tyrosine kinase inhibitors (TKIs), such as imatinib, nilotinib, and dasatinib, are currently the front-line treatment options for CML. Recently, natural killer (NK) cell activation and expansion have been shown to be associated with the optimal molecular responses of TKI treatments for CML. To investigate the effects and mechanisms of these TKIs on NK cells, sorted CD3-CD16+CD56dim and CD3-CD16+CD56bright NK cells from CML patients in chronic phase (CP) were characterized by their expressions of NK activating and inhibitory receptors. The expressions of activating receptors including NKG2D, natural cytotoxicity receptor (NCR) and DNAM-1, increase equally during the TKI treatments for CML. In this report, we uncovered that the levels of inhibitory receptors, such as NKG2A and killer cell immunoglobulin-like receptor (KIR) 3DL1, were significantly lower on NK cells in the CML patients treated with dasatinib than in the patients treated with imatinib or nilotinib. Interestingly, CML patients treated with dasatinib expressed fewer NKG2A+ NK cells, which provide negative signals for NK-mediated cytotoxicity. For these dasatinib-treated patients, the duration to achieve the major molecular response (MMR) also was significantly correlated with NKG2A+ NK cell expression. These unique effects on NKG2A expression were not observed in patients on imatinib or nilotinib. In line with NKG2A down-regulation by dasatinib, NK-cell cytotoxicity evaluated by the killing assay was significantly higher in patients treated with dasatinib than in those treated with imatinib or nilotinib. The lower NK cytotoxicity in patients treated with imatinib or nilotinib could be restored by NKG2A blockade using anti-NKG2A antibody. Further in vitro experiments revealed mechanistically that dasatinib could inactivate p38 mitogen-activated protein kinase (MAPK), and consequently affect nuclear localization of GATA-3 and expression of NKG2A. Our results highlight the dual effects of dasatinib in direct inhibition of ABL kinase and in immunomodulation through down-regulating the NKG2A+ NK population, contributing to the shorter optimal molecular responses (MR) during CML treatments.